Directory of training specialists - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Directory of training specialists in agricultural information compiled by Jane Johnson and N William Posnett 1993 188pp ISBN 92 9081 086 6 available from CTA.